Collective resistance despite complicity: High identifiers rise above the legitimization of disadvantage by the in‐group. (17th January 2017) - Jiménez‐Moya, Gloria; Rodríguez‐Bailón, Rosa; Spears, Russell; de Lemus, Soledad
Abstract : How do individuals deal with group disadvantage when their fellow in‐group members conceive it as legitimate? Integrating research on the normative conflict model (Packer, 2008, Pers. Soc. Psychol. Rev., 12, 50) and collective action, we expect high identifiers to reject the in‐group norm of legitimacy that justifies the inequality, and to assert that the group is actually able and willing to contest the disadvantage by collective means. In Study 1 and Study 2, we tested this hypothesis in different intergroup contexts. The results confirmed our predictions and also showed one boundary condition for high identifiers, namely that the content of the social identity supports resistance. In Study 3, we found support for our hypothesis using artificial groups and manipulating identification experimentally. These results show that even when a disadvantaged group appears to accept its situation, high identified in‐group members will still contest this and, moreover, expect other in‐group members to support them in this endeavour.